2012
DOI: 10.1074/jbc.m112.373308
|View full text |Cite
|
Sign up to set email alerts
|

Base of the Measles Virus Fusion Trimer Head Receives the Signal That Triggers Membrane Fusion

Abstract: Background: A homology model of the trimeric measles virus fusion protein predicts a cavity in the base of the head. Results: Hydrophobic residues required for interactions with the hemagglutinin map to this cavity. Conclusion:The base of the measles virus fusion protein trimer head receives the signal that triggers membrane fusion. Significance: Emerging, re-emerging, and prevalent paramyxoviruses may operate based on similar signal transmission mechanisms.The measles virus (MV) fusion (F) protein trimer exec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
52
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 49 publications
3
52
0
Order By: Relevance
“…This model is substantiated by the finding that truncated, stabilized MeV H stalks lacking the head domains are sufficient to specifically trigger MeV F (31). Several residues and/or microdomains in the F head domains are suggested to participate in H binding (29,(32)(33)(34)(35).…”
mentioning
confidence: 53%
“…This model is substantiated by the finding that truncated, stabilized MeV H stalks lacking the head domains are sufficient to specifically trigger MeV F (31). Several residues and/or microdomains in the F head domains are suggested to participate in H binding (29,(32)(33)(34)(35).…”
mentioning
confidence: 53%
“…On the basis of the interface propensity and the conservation of physical chemical properties among F proteins, it has been proved that six residues at the base of the MV F head region receive the signal from the MV H protein (31), suggesting that these residues are involved in the H-F interaction. It is worth noting, in this context, that two (Q322 and E325) of the identified six residues correspond to T312 and L315 in PIV5 F segment R, respectively (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in the region 391-420, a single mutation of N403D resulted in a loss of fusion activity and binding reactivity with conformational specific antibody, suggesting that aspartate (the assignment found in AKO and Ban 010) plays a major role in downregulating fusion activity by altering the conformation of the F protein. Recent studies also suggested that this domain may be critical in F and HN interactions or F and H interactions for measles, PIV5 and SV41 (Apte-Sengupta et al, 2012;Bose et al, 2013). It will be of interest in future studies to evaluate whether the N403D mutation affects any of the specific stages of NDV fusion activity and the interaction between the F and HN proteins.…”
mentioning
confidence: 99%